Saint Thomas Aquinas' ontological epistemology as clarified realism: The relating of subject to object for ontological knowledge. Issue 3 (2nd September 2016) - David Scott, Callum
Abstract : The Kantian revolution limited the possibility of ontological knowledge, severing subject from thing as is evident in its legacy in both continental and analytic philosophy. Consequently, if a thing cannot be known as it is, the philosophical status of empirical science as a study about existing natural things should be called into question. It could be construed, for instance, that a scientific theory is a construction about something to which the subjective constructor can never have ontological access. But, when empirical scientists develop evidence-based proofs for their theories the assumption of realism usually stands: scientific theories constructed by scientists are actually purported to represent natural entities back to these constructing scientists. Given that there is a danger of philosophy becoming isolated from empirical science, we attempt to bridge the gap between philosophical discourse and science-in-praxis through a recapitulation of Aquinas' ontological epistemology. Aquinas argued for a clarified realism in which the epistemic is construed as an intersection between the thinking subject and the object. Contrary to naïve realism, then, it will be explicated how Aquinas' realism was a precursor of "critical realism", as he discerned the complex interaction of thinking subject and the being of the object as both bearing on the production of knowledge.